PENGARUH PENGETAHUAN KEUANGAN, SIKAP KEUANGAN DAN KEPRIBADIAN TERHADAP PERILAKU KEUANGAN PADA PELAKU UMKM KAIN TENUN RONGKONG - Maulidsa Qadyannu; Hety Budiyanti; Nurman (JURNAL BISNIS KOLEGA, 2022)
This study aims to determine how the influence of financial knowledge, financial attitudes, and personality on financial management behavior in Rongkong woven fabric MSME actors. The type of research used in this study is a quantitative approach. The population in this study was a woven fabric craft center in Rongkong Village, North Luwu Regency with 80 people and all of them were taken as samples. Data collection techniques in research are library research, observation, and questionnaires. The data analysis technique used in this research is descriptive statistical analysis and inferential statistics with the help of the SPSS version 26 software program. The results of this study indicate that financial knowledge has no effect on financial management actors, while financial attitudes and personality have a significant effect on financial management actors on Rongkong woven fabric MSME actors.